(untitled) - Wybenga, George L. (Hoboken, N.J., 2006)
The Third Edition continues its long tradition as a useful tool in the ever-changing world of packaging design. It features more than fifty new patterns and new material on the latest advances in closures. This hands-on resource gives designers the advantage they need to successfully meet any packaging challenge. Every pattern has been test-constructed to verify dimensional accuracy and is ready to be traced, scanned, or photocopied for immediate use.
Keywords: Packaging,Paperboard,Đóng gói,Cáctông; Design,Thiết kế